Uma leitura simbólica do espírito empreendedor - Dado, Salem, (2006)
This study investigates the symbolic meaning of the entrepreneurial spirit by means of the interpretation of The Lusiads by Luis de Camões, a poetic work piece that examines the Portuguese enterprise through the opening of a commercial route with the Orient. The work begins with an elucidation of the character of the entrepreneur through various perspectives: etymology, characterization, participation in the capitalist economic policy and motivation. Following this, as a justification to the utilization of a poetic work for the investigation of the theme, an exploration of poets and their interpretation of reality is undergone. Camões work is divided in to five episodes: The Departure; Adamastor, the Giant; The Path of Trials and the Divine Interference; Arrival at the Orient; The Return - The Island of Loves. The interpretation is accomplished through the use of central concepts of analytical psychology such as the process of individuation and the heroes journey. Finally, the author raises issues quoting practical cases of his professional experience, demonstrating that businesses work as projective field of the psyche of the entrepreneurs who unconsciously seek individuation within their enterprises. Furthermore, a few typical collective behaviors of economies centered in the capitalist entrepreneurial spirit are presented